Between saying and doing towards an analytic pragmatism - Brandom, Robert (Oxford : Oxford University Press, 2008)
'Between Saying and Doing' reconciles pragmatism with analytic philosophy. Robert Brandom investigates the relations between the meaning of linguistic expressions (logical, indexical modal, normative, and intentional, among others) and their use. He offers new ways of thinking about empiricism, naturalism, and functionalism.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pragmatism; Analysis (Philosophy)